“Determinación de parámetros tecnológicos para obtención de harina de papa aérea (dioscorea bulbifera L.) Ñame Congo” - Cortegana Pizarro, David (2000)
He present work of research is conducted with the purpose of establish them parameters appropriate for the obtaining of flour of Papa air (Dioscorea bulbifera L.) through dried with air hot, using dryer of trays with circulation of air by convection forced and flow parallel. He understood the study of 1a raw material, starch, the process and the final product, making as appropriate physicochemical, rheological assessments, microbiological and sensory. The air Potato tubers (Dioscorea bulbi.fera l.) reported high total carbohydrate content (88.6548% b.s.), starch / "{5 <: OQ59 - _}(